(untitled) (Central Medical College Journal, 2023)
Background: Regional anesthesia is preferred in most of the chronic obstructive pulmonary disease (COPD) patients to avoid intra- and postoperative complications related to general anesthesia. Herein we reported a case of empyema gall bladder with severe COPD who went for an open cholecystectomy under thoracic segmental spinal with epidural anesthesia. He had substantial dyspnea on routine household activities (NYHA Class III). He had history of several hospital admissions with acute onset of dyspnea and was treated with bronchodilators and systemic steroids. He had no history of other comorbidity. The patient was scheduled for an emergency laparotomy followed by open cholecystectomy. Postoperative recovery was uneventful allowing the patient to be discharged on the 5th POD. Central Medical College Journal Vol 6 No 2 Jauly 2022 Page: 97-100